FOLLOWING THE YELLOW BRICK ROAD An investigation into entrepreneurial opportunity recognition and growth firm developmental challenges - Barker, Nicholas (2007)
The aim of this project is to understand how and where the entrepreneur finds new business ideas and how these ideas are put into practice. The report then explores the difficulties the entrepreneur may encounter in growing a new firm into a larger business.